A kind of ammonium bifluoride electrolyte and its processing electrolytic process of beryllium copper surface

CN120967484BActive Publication Date: 2026-10-30KUNSHAN YIDING IND TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511295080.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-11
Publication Date
2026-10-30
Estimated Expiration
2045-09-11

AI Technical Summary

Technical Problem

[0006]针对现有技术存在的常规使用的氢氟酸和硝酸混酸体系存在的技术难关问题,一方面,对操作人员和操作环境所存在的重大安全隐患问题,另一方面,对金属表面处理连续生产中的产品质量难于维持稳定的问题

Benefits of technology

本发明是一种操作安全可靠、清洁环保型的电解溶液,替代现有技术常规使用的氢氟酸和硝酸混酸体系,一方面,解决了对操作人员和操作环境所存在的重大安全隐患问题,另一方面,解决了对金属表面处理连续生产中的产品质量难于维持稳定的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120967484B_ABST
    Figure CN120967484B_ABST
Patent Text Reader

Abstract

The application discloses a kind of ammonium bifluoride electrolyte, with pure water as solvent, containing 6.1-10.3g ammonium bifluoride, 2.2-4.2g ammonium fluoride, 2.9-4.9g sodium fluoride, 0.22-0.42g 2,5,8,11-tetramethyl-6-dodecyn-5,8-diol per liter of electrolyte;For treating beryllium copper surface, including the following steps: (1) the ammonium bifluoride electrolyte is placed in the electrolytic cell of electrolytic equipment;(2) the beryllium copper piece to be treated is placed in the electrolyte of step (1) as anode, stainless steel plate as cathode, electrolysis under the action of direct current;(3) the beryllium copper piece after electrolytic treatment is rinsed with pure water, and then placed in plating solution for nickel plating;(4) the beryllium copper piece after nickel plating treatment is rinsed with pure water, and dried to remove surface moisture, to obtain the surface treated beryllium copper piece.The application is safe and reliable in operation, clean and environmentally friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to electrochemical surface treatment technology, and in particular to an ammonium fluoride electrolyte and its electrolytic process for treating beryllium copper surfaces. Background Technology

[0002] Beryllium copper C17200 is the highest-performance copper alloy raw material for high-end electronic products. It possesses a range of excellent physical, chemical, and mechanical properties, including high strength, elasticity, fatigue strength, hardness, low elastic hysteresis, corrosion resistance, wear resistance, cold resistance, high electrical conductivity, non-magnetic properties, and no sparking upon impact. Therefore, it is widely used as a raw material in the semiconductor leadframe-chip industry chain for manufacturing various electronic products.

[0003] Because beryllium copper contains a variety of trace metallic elements, among which beryllium is the most reactive, it forms very stable beryllium oxide on the surface of beryllium copper materials. On the one hand, the stability of beryllium oxide plays a good protective role, preventing the material from being further oxidized or corroded by corrosive substances. On the other hand, in the upstream surface treatment industry of the semiconductor lead frame-chip industry chain, removing beryllium oxide from the surface of semiconductor lead frames has become a very difficult processing step.

[0004] Currently, in the surface treatment process of semiconductor lead frames, patent CN 112176371 A discloses a beryllium copper acid activation treatment method. In order to remove beryllium oxide from the surface of the metal material, a mixture of nitric acid and hydrofluoric acid is used to immerse the beryllium copper part. The solvent of the acid solution is water, and the solutes are nitric acid and hydrofluoric acid, wherein the concentration of nitric acid is 200 ml / L and the concentration of hydrofluoric acid is 100 ml / L.

[0005] Because hydrofluoric acid is highly corrosive and volatile, and nitric acid is a strong oxidizing agent that easily decomposes and releases harmful nitrogen dioxide gas, the commonly used mixed system of hydrofluoric acid and nitric acid poses significant safety hazards to both operators and the operating environment during use. Furthermore, the strong corrosiveness of hydrofluoric acid and the strong oxidizing properties of nitric acid are difficult to effectively and stably control during the processing of metal plating parts, creating insurmountable obstacles to the stable management of product quality. Summary of the Invention

[0006] To address the technical challenges of existing technologies using conventional mixed hydrofluoric acid and nitric acid systems, which pose significant safety hazards to operators and the operating environment, and make it difficult to maintain stable product quality in continuous metal surface treatment production, this invention provides an ammonium bifluoride electrolyte and its electrolytic process for treating beryllium copper surfaces. This invention is safe, reliable, clean, and environmentally friendly.

[0007] The technical solution of the present invention is as follows: The first objective of this invention is to provide an ammonium bifluoride electrolyte, using pure water as a solvent, wherein each liter of electrolyte contains 6.1-10.3 g of ammonium bifluoride, 2.2-4.2 g of ammonium fluoride, 2.9-4.9 g of sodium fluoride, and 0.22-0.42 g of 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol.

[0008] In one embodiment of the present invention, the ammonium bifluoride electrolyte uses pure water as a solvent, and each liter of electrolyte contains 8.2 g of ammonium bifluoride, 3.7 g of ammonium fluoride, 4.4 g of sodium fluoride, and 0.33 g of 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol.

[0009] In one embodiment of the present invention, the ammonium bifluoride electrolyte uses pure water as a solvent, and each liter of electrolyte contains 8.0 g of ammonium bifluoride, 3.0 g of ammonium fluoride, 3.7 g of sodium fluoride, and 0.3 g of 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol.

[0010] The second objective of this invention is to provide an electrolytic process for treating the surface of beryllium copper with the above-mentioned ammonium bifluoride electrolyte, comprising the following steps: (1) Place the above-mentioned ammonium bifluoride electrolyte into the electrolytic cell of the electrolysis equipment; (2) The beryllium copper part to be treated is placed in the electrolyte described in step (1) as the anode and the stainless steel plate as the cathode, and electrolyzed under the action of direct current; (3) Rinse the electrolytically treated beryllium copper parts with pure water, and then place them in an electroplating solution to plate nickel; (4) Rinse the nickel-plated beryllium copper parts with pure water, dry them to remove surface moisture, and you will get surface-treated beryllium copper parts.

[0011] In one embodiment of the present invention, in step (1), the electrolysis equipment includes an electrolysis control system and an electroplating condition monitoring system; The electrolysis control system includes an electrolytic cell, a solution heater, and a power supply; The electrolysis condition monitoring system automatically analyzes the composition of raw materials in the electrolyte and replenishes them at regular intervals to maintain a small change in the concentration of raw materials in the electrolyte, thereby achieving the electrolytic removal of oxides from the surface of beryllium copper to be treated.

[0012] In one embodiment of the present invention, in step (2), the beryllium copper part to be processed is a circular metal needle.

[0013] In one embodiment of the present invention, the beryllium copper component to be processed consists of nine circular metal pins arranged in parallel to form a basic device unit; then the basic device unit is arranged in a 6-by-3 configuration to form a semiconductor lead frame electronic product experimental chip.

[0014] In one embodiment of the present invention, in step (2), the cathode is stainless steel 316.

[0015] In one embodiment of the present invention, in step (2), the electrolysis current is 100~400 mA and the electrolysis time is 18~30 s.

[0016] Preferably, the electrolysis current is 250 mA and the electrolysis time is 24 s.

[0017] In one embodiment of the present invention, in step (2), the following reaction occurs on the anode and cathode surfaces: Beryllium copper component as anode: BeO+2NH4HF2=(NH4)2BeF4+H2O formula 1 CuO+2NH4HF2=(NH4)2CuF4+H2O Formula 2 In Formula 1, the beryllium copper part contains no more than 2% beryllium. The trace amount of beryllium oxide BeO formed on the surface of the beryllium copper part reacts with ammonium bifluoride NH4HF2 to generate ammonium fluoroberyllate (NH4)2BeF4, which is easily soluble in water. In Formula 2, the trace amount of copper oxide CuO formed on the surface of the beryllium copper part reacts with ammonium bifluoride NH4HF2 to generate ammonium fluorocubic acid (NH4)2CuF4, which is easily soluble in water. 316 stainless steel as cathode: Cu 2+ →Cu formula 3 In Formula 3, the divalent copper ions Cu in the electrolyte 2+ The electrons are reduced to copper atoms Cu by the 316 stainless steel cathode plate and adhere to the surface of the 316 stainless steel cathode.

[0018] Ammonium bifluoride (NH4HF2), under the action of an electric field, reacts with beryllium oxide and copper oxide on the surface of beryllium copper parts through formulas 1 and 2, thereby removing metal oxides and cleaning the surface of beryllium copper parts. Ammonium fluoride (NH4F) is a stabilizer for electrolyte solutions. In aqueous solution, ammonium fluoride (NH4F) exists as ammonia ions (NH4+). + and fluoride ions F - The fluoride ion F exists in the form of - In Formulas 1 and 2, ammonium bifluoride (NH4HF2) acts to prevent decomposition and stabilize it. Simultaneously, excess fluoride ions promote the reaction of ammonium bifluoride (NH4HF2) with beryllium oxide and copper oxide towards the products ammonium fluoroberyllate (NH4)2BeF4 and ammonium fluorocubic acid (NH4)2CuF4. Meanwhile, ammonia ions (NH4)... + F ions - It also has a stabilizing effect on both Formula 1 and Formula 2; Sodium fluoride (NaF) is a conductive salt in electrolytic solutions. In aqueous solution, sodium fluoride (NaF) completely ionizes into sodium ions (Na+). + and fluoride ions F - The fluoride ion F exists in the form of - The ammonium hydrogen fluoride NH4HF2 in Formula 1 and Formula 2 plays a role in preventing decomposition and stabilizing it. At the same time, the excess fluoride ions help the ammonium hydrogen fluoride NH4HF2 to react with beryllium oxide and copper oxide to promote the reaction towards the products ammonium fluoroberyllate (NH4)2BeF4 and ammonium fluorocubic acid (NH4)2CuF4. 2,5,8,11-Tetramethyl-6-dodecyne-5,8-diol is an additive for the electrolyte solution. Through the hydrophilic functional groups of the two hydroxyl groups of the diol, it reduces the bubbles generated during the chemical reactions of formulas 1 to 3 and lowers the surface tension of the beryllium copper parts during the chemical reactions of formulas 1 and 2, thus playing a wetting and affinity role.

[0019] In one embodiment of the present invention, in step (2), the surface area of ​​the beryllium copper part to be processed is... S (cm) 2 Current density of the electrolyte solution D (mA / cm) 2 The settings, and the current of the electrolytic power supply. A (mA) has the following relationship: A = D · S Formula 4 beryllium copper component surface area to be processed S (cm) 2 The number of moles of beryllium oxide on its surface M 氧化铍 (mol) and the number of moles of copper oxide M 氧化铜 The (mol) content is shown in Formulas 5 and 6: M 氧化铍 = M 铍 = W 铍 / Beryllium atomic weight = ρ 铍 · V / Beryllium atomic weight = ρ 铍 · S 铍 · h / Beryllium atomic weight formula 5 In formula 5, M 氧化铍 The molar number of beryllium oxide (mol)M 铍 The molar number of beryllium atoms (mol) W 铍 This represents the weight of beryllium (g). V 铍 beryllium volume (cm³) 3 ), ρ 铍 beryllium specific gravity (g / cm³) 3 ), S 铍 beryllium surface area (cm²) 2 ), h 铍 The thickness of the beryllium surface (cm); M 氧化铜 = M 铜 = W 铜 / Atomic weight of copper = ρ 铜 · V / Atomic weight of copper = ρ 铜 · S · h / Copper Atomic Weight Formula 6 In formula 6, M 氧化铜 The molar number of copper oxide (mol) M 铜 The molar number of copper atoms (mol). W 铜 The weight of copper is (g). V 铜 Volume of copper (cm³) 3 ), ρ 铜 The specific gravity of copper (g / cm³) 3 ), S 铜 Copper surface area (cm²) 2 ), h 铜 The thickness of the copper surface (cm); Based on the molar content of beryllium oxide and copper oxide, and according to the reaction relationship in Formulas 1 and 2, the daily amount of ammonium fluoride required can be calculated using the molar content of beryllium oxide and copper oxide in the beryllium copper parts to be treated and the daily production quantity.

[0020] Based on the molar amounts of beryllium oxide and copper oxide, and according to the reaction relationships in formulas 1 and 2, in order to maintain the stability of continuous electrolytic production, the molar amount of ammonium fluoride consumed for 8-24 hours of continuous production is set.W 消耗氟化氢铵 The weight of ammonium bifluoride in the prepared electrolyte solution was lower than the weight of the electrolyte solution. W 配制氟化氢铵 For amounts below 5%, it is represented by Formula 7 as follows: W 消耗氟化氢铵 / W 配制氟化氢铵 <5% Formula 7.

[0021] In one embodiment of the present invention, in step (3), the solvent in the electroplating solution is pure water, including nickel aminosulfonate with a concentration of 90 g / L (calculated as nickel), nickel chloride 10 g / L, boric acid 45 g / L, additives 1.5 ml / L, and pH 4.0.

[0022] In one embodiment of the present invention, in step (3), the conditions for nickel plating are: current of 12.6 amperes; plating time of 158 s; and nickel plating film thickness of 3.1~3.2 μm.

[0023] The beneficial technical effects of this invention are as follows: This invention provides a safe, reliable, clean, and environmentally friendly electrolytic solution that replaces the conventionally used hydrofluoric acid and nitric acid mixed acid system. On the one hand, it solves the major safety hazards to operators and the operating environment; on the other hand, it solves the problem of maintaining stable product quality in continuous production of metal surface treatment. Attached Figure Description

[0024] Picture 1 This is a schematic diagram of the basic device unit of the beryllium copper part to be processed in this invention.

[0025] Picture 2 This is a schematic diagram of the experimental semiconductor lead frame electronic product of the present invention.

[0026] Picture 3 This is a schematic diagram of the electrolysis equipment of the present invention.

[0027] Picture 4 This is a schematic diagram of single metal needle detection in Embodiment 1 of the present invention.

[0028] Picture 5 This is a schematic diagram of the winding and bending detection in Embodiment 1 of the present invention.

[0029] Picture 6 This is a schematic diagram of single metal needle detection in Embodiment 4 of the present invention.

[0030] Picture 7 This is a schematic diagram of the winding and bending detection in Embodiment 4 of the present invention.

[0031] Picture 8This is a schematic diagram of single metal needle detection in Comparative Example 1 of the present invention.

[0032] Picture 9 This is a schematic diagram of the winding and bending detection of Comparative Example 1 of the present invention.

[0033] Picture 10 This is a schematic diagram showing the optimization results of the electrolytic solution current conditions in this invention.

[0034] Picture 11 This is a schematic diagram of single metal needle detection in Embodiment 8 of the present invention.

[0035] Picture 12 This is a schematic diagram of the winding and bending detection in Embodiment 8 of the present invention.

[0036] Picture 13 This is a schematic diagram of single metal needle detection in Embodiment 11 of the present invention.

[0037] Picture 14 This is a schematic diagram of the winding and bending detection in Embodiment 11 of the present invention.

[0038] Picture 15 This is a schematic diagram of single metal needle detection in Comparative Example 8 of the present invention.

[0039] Picture 16 This is a schematic diagram of the winding and bending detection of Comparative Example 8 of the present invention.

[0040] Picture 17 This is a schematic diagram showing the optimized electrolyte composition ratio of the present invention.

[0041] Picture 18 This is a schematic diagram of single metal needle detection in Embodiment 18 of the present invention.

[0042] Picture 19 This is a schematic diagram of the winding and bending detection in Embodiment 18 of the present invention.

[0043] Picture 20 This is a schematic diagram of a single metal needle for invention comparative example 18.

[0044] Picture 21 This is a schematic diagram of the winding and bending detection for Comparative Example 18 of the Invention.

[0045] Picture 22 This is a schematic diagram showing the optimized concentration of the additive in the electrolyte solution according to the present invention.

[0046] Picture 23 This is a schematic diagram of single metal needle detection in Embodiment 25 of the present invention.

[0047] Picture 24 This is a schematic diagram of the winding and bending detection in Embodiment 25 of the present invention.

[0048] Picture 25 This is a schematic diagram of single metal needle detection in Comparative Example 24 of the present invention.

[0049] Picture 26 This is a schematic diagram of the winding and bending detection of Comparative Example 24 of the present invention.

[0050] Picture 27 This is a schematic diagram showing the optimized electrolysis time of the electrolyte solution of the present invention.

[0051] Among them, 101 is the basic device unit of beryllium copper parts to be processed; 100 is the experimental piece of electronic product with semiconductor lead frame; 200a is the right electrolytic cathode; 200b is the left electrolytic cathode; 300 is the electrolytic solution tank; and 500 is the electrolysis equipment. Detailed Implementation

[0052] The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0053] like Picture 1 This is a schematic diagram of the basic component unit of the beryllium copper part to be processed. The material is C17002 beryllium copper (average beryllium content 2%, average copper content 96.7%, surface beryllium oxide and copper oxide film thickness both 2 μm). It has 9 circular metal needles, each 72.8 mm long and 1.38 mm in diameter. The metal needles are fixed by two metal strips of the same material: an upper strip and a lower strip with positioning holes. The area of ​​the 9 circular metal needles is: 9 × 72.8 × (1.38 / 2). 2 ×3.14 = 979.49 mm 2 The area of ​​the upper strip plus the area of ​​the lower strip with the positioning hole = 70.5 × 0.53 × 2 + 70.5 × 0.74 × 2 = 179.07 mm 2 Therefore, the area of ​​the basic device unit 101 is 979.49 mm². 2 +179.07 mm 2 =1158.56 mm 2 ; like Picture 2 A schematic diagram of a semiconductor leadframe electronic product experimental piece, consisting of 18 basic beryllium copper components to be processed, arranged in a 6-by-3 grid; the area of ​​the experimental piece = 18 units + outer frame = 18 × 1158.56 + (415.5 - 407.3) × (253.5 - 243.7) × 2 = 21014.8 mm. 2 =210.148 cm 2 .

[0054] In the following examples and comparative examples, during the nickel plating process, the solvent in the electroplating solution was pure water, including nickel sulfamate with a concentration of 90 g / L (calculated as nickel), nickel chloride 10 g / L, boric acid 45 g / L, additives 1.5 ml / L, and pH 4.0; the nickel plating conditions were: current 12.6 amperes; plating time 158 s; and nickel plating film thickness of 3.1~3.2 μm.

[0055] Test method: 1. The adhesion of the metal coating was tested in accordance with the national standard GB / T 5270-2005 "Review of test methods for adhesion strength of electrodeposited and chemically deposited metal coatings on metal substrates"; Test method: A nickel-plated beryllium copper circular metal needle is bent and wrapped around the surface three times. The condition of the bent surface is observed under 140x magnification. Judgment criteria: The judgment is based on the proportion of the area where the plating has peeled off. Ni 镀层脱落面积 / Ni 镀层总面积 =0 Excellent 0 < Ni 镀层脱落面积 / Ni 镀层总面积 ≤1% Good 1% < Ni 镀层脱落面积 / Ni 镀层总面积 <5% qualified 5% ≤ Ni 镀层脱落面积 / Ni 镀层总面积 Unqualified 2. Visual inspection of nickel-plated beryllium copper circular metal needles; Smooth and flat surface Surface pitting is unacceptable. Surface unevenness is unacceptable. 3. Comprehensive judgment based on nickel-plated beryllium copper circular metal needles; Smooth and flat surface with no exposed copper. Surface pitting + (no) exposed copper is unacceptable Surface unevenness + (no) exposed copper is unacceptable Examples 1-7 Reference Picture 3 An electrolytic process for treating beryllium copper surfaces with an ammonium bifluoride electrolyte includes the following steps: (1) The semiconductor lead frame electronic product test piece is degreased by ultrasonic degreasing and electrolytic degreasing, and then thoroughly cleaned with pure water; (2) Place 200L of ammonium hydrogen fluoride electrolyte in the electrolytic cell of the electrolysis equipment; the concentration of ammonium hydrogen fluoride NH4HF2 in the ammonium hydrogen fluoride electrolyte is 8.0 g / L, the concentration of ammonium fluoride NH4F is 3.0 g / L, the concentration of sodium fluoride NaF is 3.7 g / L, and the concentration of 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol is 0.3 g / L; (3) Place the semiconductor lead frame electronic product experimental chip in the electrolyte described in step (2) as the anode and stainless steel 316 as the cathode, and electrolyze for 20 s under the action of direct current; (3) Rinse the electrolytically treated beryllium copper parts with pure water, and then place them in an electroplating solution to plate nickel with a coating thickness of 3.0 μm; (4) Rinse the nickel-plated beryllium copper parts with pure water, dry them to remove surface moisture, and you will get surface-treated beryllium copper parts.

[0056] The current conditions and test results in Examples 1-7 are shown in Table 1 below: Table 1

[0057] The ratio of the area of ​​coating peeling to the total area of ​​coating is: Ni 镀层脱落面积 / Ni 镀层总面积 As shown in Table 1, the current conditions for Examples 1-7 are in the range of 100mA to 400mA, i.e., the current density. D The range is 0.48~1.90 mA / cm 2 Under stable conditions, maintaining a nickel-plated sample film thickness of 3.11~3.19 μm, the beryllium copper metal needles obtained in Example 1 were magnified 140 times, and the detection results are as follows: Picture 4 , 5 As shown, its surface is smooth and flat with no exposed copper, and the ratio of the area of ​​plating peeling off to its total area is... Ni 镀层脱落面积 / Ni 镀层总面积 The value was 0.0%; therefore, its overall judgment result was excellent. Examples 2-7, using the same testing method as Example 1, also all yielded excellent overall judgment results. The beryllium copper metal needle obtained in Example 4, when magnified 140 times, and the resulting samples were examined. Picture 6 , 7 As shown, its nickel-plated surface is smooth and flat with no exposed copper, and the ratio of the area of ​​plating peeling off to the total area of ​​plating is... Ni 镀层脱落面积 / Ni 镀层总面积0.0%; therefore, the corresponding 250mA is taken as the optimal current condition.

[0058] Comparative Examples 1-7 Similar to Example 4, the only difference is that the current conditions set for Comparative Examples 1 to 7 are shown in Table 2 below. The test results are also shown in Table 2.

[0059] Table 2

[0060] The ratio of the area of ​​coating peeling to the total area of ​​coating is: Ni 镀层脱落面积 / Ni 镀层总面积 Table 2 shows that when the current value of the electrolytic power supply is set to be below 100 mA or above 400 mA, and the nickel-plated sample film thickness is maintained at a stable state of 3.12~3.18 μm, the beryllium copper metal needles obtained in Comparative Example 2, when magnified 140 times, show numerous pits and exposed copper, with a larger area than the sample obtained in Comparative Example 2. Ni 镀层脱落面积 / Ni 镀层总面积 The result was 7.2%, which was deemed unqualified. The overall judgment results for Comparative Examples 3-7 were all unqualified. Comparative Example 1 was the test result with the electrolysis power supply off and no electrolysis performed. Under the condition that the processing time was increased to 40 seconds, the beryllium copper metal needles obtained from Comparative Example 1 were magnified 140 times, and the test results are as follows: Picture 8 , 9 As shown in the test results, there is a lot of exposed copper, and its area is larger than that of copper. Ni 镀层脱落面积 / Ni 镀层总面积 The result was 13.3%, which was deemed unqualified.

[0061] In summary, the electrolyte solution of this invention cannot be applied under non-electrolytic conditions without electricity. Furthermore, under the selected electrolysis treatment time of 20s, the low current of 20~50 mA is insufficient to completely remove beryllium oxide and copper oxide. Similarly, under the high current of 500~600 mA, the surface of the semiconductor lead frame electronic product experimental chip undergoes excessive reaction, causing the surface to develop towards a rough surface trend, resulting in pitting and exposed copper on the nickel-plated surface.

[0062] Electrolysis current and the ratio of the area of ​​plating peel off to the total area of ​​plating ( Ni 镀层脱落面积 / Ni 镀层总面积 The relationship is as follows: Picture 10 As shown, from Picture 10It is known that when the electrolytic solution of the present invention is actually applied to the beryllium copper semiconductor lead frame electronic product experimental piece, even when the electrolytic power supply is stopped, i.e., the processing time of Comparative Example 1 is increased to twice the set condition of 40 seconds, the beryllium oxide and copper oxide on the surface of the semiconductor lead frame electronic product experimental piece cannot be completely removed. This results in the bonding force between the nickel plating layer and the surface of the semiconductor lead frame electronic product experimental piece not being very strong. Therefore, after bending and winding into a circle, the nickel plating layer cracks and peels, exposing the surface of the beryllium copper material.

[0063] The test results for Comparative Examples 2-4, with currents ranging from 20 to 50 mA, show that as the electrolysis current increases, the ratio of the area of ​​plating peel off to the total area of ​​plating decreases. Ni 镀层脱落面积 / Ni 镀层总面积 The adhesion of the nickel plating layer decreases sequentially from 7.20%, 2.70%, to 0.50%, indicating that the adhesion of the nickel plating layer becomes stronger and stronger. The test results for Examples 1-7, with currents ranging from 100 to 400 mA, show the ratio of the area of ​​plating layer peeling to the total area of ​​the plating layer. Ni 镀层脱落面积 / Ni 镀层总面积 Maintaining a value of 0.0% indicates excellent adhesion of the nickel plating layer; the ratio of the area of ​​plating peeling off to the total area of ​​the plating layer is shown in the test results where the current is continuously increased from Comparative Examples 5-7 to 500-700 mA. Ni 镀层脱落面积 / Ni 镀层总面积 The current was continuously increased from 0.30%, 0.60% to 1.30%, starting from Comparative Example 5. The current had exceeded the upper limit of the optimal range. Therefore, the excessive current intensity began to accelerate the electrolysis of the beryllium copper surface, causing its surface to develop in the direction of roughness, resulting in pitting and exposed copper on the surface after nickel plating.

[0064] Examples 8-14 Same as Example 4, except that the concentration of additive 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol is 0.35 g / L, and the electrolyte composition is shown in Table 3 below.

[0065] Table 3

[0066] The ratio of the area of ​​coating peeling to the total area of ​​coating is: Ni 镀层脱落面积 / Ni 镀层总面积 As shown in Table 3, the concentrations of ammonium bifluoride, ammonium fluoride, and sodium fluoride in Example 8 were 6.1 g / L, 2.2 g / L, and 2.9 g / L, respectively. Under stable conditions with a nickel-plated sample film thickness of 3.15 μm, the beryllium copper metal needles obtained in Example 8, both single and wound, were magnified 140 times. The detection results are as follows: Picture 11 , 12 As shown, its surface is smooth and flat with no exposed copper, and the ratio of the area of ​​plating peeling off to its total area is... Ni 镀层脱落面积 / Ni 镀层总面积 The value was 0.0%; therefore, its overall judgment result was excellent; the overall judgment results of Examples 9 to 14 were also excellent. The beryllium copper metal needle obtained in Example 11, when magnified 140 times, and the results are as follows: Picture 13 , 14 As shown in the test results, the nickel-plated surface is smooth and flat with no exposed copper, and the ratio of the area of ​​plating peeling off to the total area of ​​plating is... Ni 镀层脱落面积 / Ni 镀层总面积 0.0%; The concentrations of ammonium bifluoride, ammonium fluoride, and sodium fluoride in Example 11 were 8.2 g / L, 3.7 g / L, and 4.4 g / L, respectively, as the optimal preparation ratio conditions.

[0067] Comparative Examples 8-13 Same as Example 11, except that the composition of the electrolyte solution is shown in Table 4 below.

[0068] Table 4

[0069] The ratio of the area of ​​coating peeling to the total area of ​​coating is: Ni 镀层脱落面积 / Ni 镀层总面积 Table 4 shows that when the concentrations of ammonium bifluoride, ammonium fluoride, and sodium fluoride in Comparative Examples 8-10 were changed, while maintaining a stable film thickness of 3.12-3.17 μm for the nickel-plated samples, the results, magnified 140 times, showed that the surfaces of the single needle and the wound nickel-plated samples exhibited an uneven, pitted appearance and exposed copper. The area ratio of these samples was... Ni 镀层脱落面积 / Ni 镀层总面积 The percentage ranged from 0.8% to 6.1%; therefore, the overall judgment result was unqualified. Comparative Examples 11-13, tested using the same method, showed the following area ratios: Ni 镀层脱落面积 / Ni 镀层总面积The percentage was 0.4% to 1.5%; therefore, the overall judgment result was unqualified. The beryllium copper metal needles obtained from Comparative Example 8, when magnified 140 times, showed the following test results: Picture 15 , 16 As shown.

[0070] Electrolyte composition and the ratio of coating peeling area to total coating area ( Ni 镀层脱落面积 / Ni 镀层总面积 The relationship is as follows: Picture 17 As shown, from Picture 17 It can be seen that when the electrolyte solution of the present invention is actually applied to beryllium copper semiconductor leadframe electronic product experimental wafers, under low concentration conditions with the preparation ratio of ammonium bifluoride, ammonium fluoride, and sodium fluoride in comparative examples 8-10, as the concentration increases, the ratio of the area of ​​plating peeling off to the total area of ​​plating also increases. Ni 镀层脱落面积 / Ni 镀层总面积 The percentage decreased sequentially from 6.10%, 3.40% to 0.80%, representing the ratio of the area of ​​coating peeling to the total area of ​​coating in Examples 8-14. Ni 镀层脱落面积 / Ni 镀层总面积 All were 0.0%; after exceeding the range described in the examples, the concentrations in Comparative Examples 11 to 13 gradually increased from 0.40% and 0.70% to 1.50%. Therefore, the electrolyte concentration ratio optimization results in Examples 8 to 14 were confirmed as the optimal range.

[0071] Examples 15-21 Same as Example 11, except that the concentration of additive 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol is shown in Table 5 below.

[0072] Table 5

[0073] The ratio of the area of ​​coating peeling to the total area of ​​coating is: Ni 镀层脱落面积 / Ni 镀层总面积 As shown in Table 5, under the additive concentration of 0.22~0.42 g / L in Examples 15~21, and with a nickel plating film thickness of 3.12~3.18 μm in a stable state, single needles and wound nickel plating samples were obtained. Detection results at 140x magnification showed that their surfaces were smooth and flat with no exposed copper, and the ratio of the plating peeling area to its total area was... Ni 镀层脱落面积 / Ni 镀层总面积The value was 0.0%; therefore, the overall judgment result was excellent; the beryllium copper metal needle obtained in Example 18, when magnified 140 times, showed the following test results: Picture 18 , 19 As shown in the test results, the nickel-plated surface is smooth and flat with no exposed copper, and the ratio of the area of ​​plating peeling off to the total area of ​​plating is... Ni 镀层脱落面积 / Ni 镀层总面积 0.0%; therefore, the optimal preparation conditions for its corresponding additive, 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol, are 0.33 g / L.

[0074] Comparative Examples 14-19 Same as Example 11, except that the concentration of the additive is shown in Table 6 below.

[0075] Table 6

[0076] The ratio of the area of ​​coating peeling to the total area of ​​coating is: Ni 镀层脱落面积 / Ni 镀层总面积 Table 6 shows that when the additive concentration of Comparative Examples 14-16 is low (0.13-0.19 g / L) and the additive concentration of Comparative Examples 17-19 is high (0.45-0.51 g / L), under stable conditions with a nickel-plated film thickness of 3.13-3.18 μm, the results of 140x magnification for both single-needle and wound nickel-plated samples show an uneven, pitted surface and exposed copper. The area ratio of Comparative Examples 14-16 is... Ni 镀层脱落面积 / Ni 镀层总面积 The percentage was 3.6% to 6.1%; therefore, the overall judgment result was unqualified. Comparative examples 17 to 19, tested using the same method, had area ratios of 3.6% to 6.1%. Ni 镀层脱落面积 / Ni 镀层总面积 The percentage was 0.5% to 1.8%; therefore, the overall judgment result was unqualified. The beryllium copper metal needles obtained in Comparative Example 18, when magnified 140 times, showed the following test results: Picture 20 , 21 As shown.

[0077] Picture 22 This is a schematic diagram showing the optimized concentration of the additive in the electrolyte solution according to the present invention. Picture 22It can be seen that when the electrolyte solution of the present invention is actually applied to beryllium copper semiconductor lead frame electronic product experimental wafers, when the additives in Comparative Examples 14-16 are in a low concentration range, as the concentration increases, the ratio of the area of ​​plating peeling off to the total area of ​​plating increases. Ni 镀层脱落面积 / Ni 镀层总面积 The percentage decreases sequentially from 3.60%, 0.30%, to 0.10%, representing the ratio of the area of ​​coating peeling to the total area of ​​coating in Examples 15-21. Ni 镀层脱落面积 / Ni 镀层总面积 The values ​​were all 0.0%; after exceeding the range described in the examples, the values ​​in Comparative Examples 17-19 gradually increased from 0.50%, 1.20% to 1.80%. Therefore, the results of the additive concentration optimization in Examples 15-21 were confirmed as the preferred range.

[0078] Examples 22-28 Same as Example 18, except that the range of electrolysis time is shown in Table 7; the test results are listed in Table 7.

[0079] Table 7

[0080] The ratio of the area of ​​coating peeling to the total area of ​​coating is: Ni 镀层脱落面积 / Ni 镀层总面积 As shown in Table 7, the beryllium copper electrolytic solution treatment conditions in Examples 22-28 were 18-30 seconds. Under stable conditions with a nickel-plated sample film thickness of 3.11-3.17 μm, the results of single needle and wound nickel-plated samples, magnified 140 times, showed that the surface was smooth and flat with no exposed copper. The ratio of the area of ​​plating peeling off to its total area was... Ni 镀层脱落面积 / Ni 镀层总面积 The value was 0.0%; therefore, the overall judgment results for the range were all excellent; the beryllium copper metal needle obtained in Example 25, when magnified 140 times, showed the following detection results: Picture 23 , 24 As shown.

[0081] Comparative Examples 20-25 Same as Example 18, except that the range of electrolysis time is shown in Table 8; the test results are listed in Table 8.

[0082] Table 8

[0083] The ratio of the area of ​​coating peeling to the total area of ​​coating is: Ni 镀层脱落面积 / Ni 镀层总面积 Table 8 shows that under the short electrolysis time of 12-16 s for Comparative Examples 20-22 and the long electrolysis time of 32-36 s for Comparative Examples 23-25, when the nickel-plated sample film thickness is 3.12-3.18 μm and the samples are stable, the surface of the single needle and the wound nickel-plated sample, under 140x magnification, exhibits an uneven, pitted surface and exposed copper. The area ratio of Comparative Examples 20-22 is... Ni 镀层脱落面积 / Ni 镀层总面积 The percentage was 0.1% to 2.3%; therefore, the overall judgment result was unqualified. Comparative examples 23 to 25, tested using the same method, had an area ratio of... Ni 镀层脱落面积 / Ni 镀层总面积 The percentage was 0.3% to 1.3%; therefore, the overall judgment result was unqualified. The beryllium copper metal needles obtained from Comparative Example 24, when magnified 140 times, showed the following test results: Picture 25 , 26 As shown.

[0084] Picture 27 This is a schematic diagram showing the optimized electrolysis time of the electrolyte solution of the present invention. Picture 27 It can be seen that when the beryllium copper electrolytic solution of the present invention is actually applied to beryllium copper semiconductor lead frames, under the short-time conditions of electrolysis in Comparative Examples 20-22, as the electrolysis time increases, the ratio of the area of ​​plating peel off to the total area of ​​plating increases. Ni 镀层脱落面积 / Ni 镀层总面积 The percentage decreases sequentially from 2.30%, 0.440% to 0.10%, representing the ratio of the area of ​​coating peeling to the total area of ​​coating in Examples 22-28. Ni 镀层脱落面积 / Ni 镀层总面积 Since all values ​​were 0.0%, after exceeding the range described in the examples, the values ​​in Comparative Examples 23 to 25 gradually increased from 0.30% and 0.70% to 1.30%. Therefore, the electrolysis time optimization results in Examples 22 to 28 were confirmed as the preferred range.

[0085] The electrolytic removal of beryllium oxide and copper oxide from the surface of beryllium copper by the electrolyte solution provided by this invention can achieve good processing results for semiconductor leadframe electronic products of different sizes.

[0086] The present invention provides a safe, reliable, clean and environmentally friendly electrolytic solution that replaces the conventional hydrofluoric acid and nitric acid mixed acid system used in the prior art. On the one hand, it solves the major safety hazards to operators and the operating environment. On the other hand, it solves the problem of maintaining stable product quality in continuous production of metal surface treatment.

[0087] The embodiments provided above are not intended to limit the scope of the invention, nor are the described steps intended to limit the order of execution. Any obvious modifications made to the invention by those skilled in the art based on existing common knowledge also fall within the scope of protection defined by the claims.

Claims

1. A fluorinated ammonium bifluoride electrolyte, characterized in that, Using pure water as a solvent, each liter of electrolyte contains 6.1~10.3 g of ammonium bifluoride, 2.2~4.2 g of ammonium fluoride, 2.9~4.9 g of sodium fluoride, and 0.22~0.42 g of 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol.

2. The ammonium bifluoride electrolyte according to claim 1, characterized in that, Using pure water as a solvent, each liter of electrolyte contains 8.2 g of ammonium bifluoride, 3.7 g of ammonium fluoride, 4.4 g of sodium fluoride, and 0.33 g of 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol.

3. The ammonium bifluoride electrolyte according to claim 1, characterized in that, Using pure water as a solvent, each liter of electrolyte contains 8.0 g of ammonium bifluoride, 3.0 g of ammonium fluoride, 3.7 g of sodium fluoride, and 0.3 g of 2,5,8,11-tetramethyl-6-dodecyne-5,8-diol.

4. An electrolytic process for treating the surface of beryllium copper with the ammonium bifluoride electrolyte according to any one of claims 1-3, characterized in that, Includes the following steps: (1) The ammonium bifluoride electrolyte according to any one of claims 1-3 is placed in the electrolytic cell of the electrolysis equipment; (2) The beryllium copper part to be treated is placed in the electrolyte in step (1) as the anode and the stainless steel plate as the cathode, and electrolyzed under the action of direct current; the electrolysis current is 100~400 mA and the electrolysis time is 18~30 s; (3) Rinse the electrolytically treated beryllium copper parts with pure water, and then place them in an electroplating solution to plate nickel; (4) Rinse the nickel-plated beryllium copper parts with pure water, dry them to remove surface moisture, and you will get surface-treated beryllium copper parts.

5. The electrolysis process according to claim 4, characterized in that, In step (1), the electrolysis equipment includes an electrolysis control system and an electroplating condition monitoring system; The electrolysis control system includes an electrolytic cell, a solution heater, and a power supply; The electrolysis condition monitoring system automatically analyzes the composition of raw materials in the electrolyte and replenishes them at regular intervals to maintain a small fluctuation in the concentration of raw materials in the electrolyte.

6. The electrolysis process according to claim 4, characterized in that, In step (2), the beryllium copper part to be processed is a round metal needle.

7. The electrolysis process according to claim 4, characterized in that, In step (2), the cathode is made of stainless steel 316.

Citation Information

Patent Citations

  • Electroplating process for plating gold on beryllium copper surface

    CN112176371A

  • Method for chemical plating of nickel-phosphorus alloy on surface of beryllium-aluminum alloy

    CN110344036A

  • Plating method

    JP2020079445A